Goma de soja na alimentação de frangos de corte: digestibilidade e desempenho - Akechi, Bruno Vinícius [UNESP] (2015)
The experiment was conducted at the Poultry Section of the Universidade Estadual Paulista Julio de Mesquita Filho (UNESP), Campus School of Engineering of Ilha Solteira, to evaluate the inclusion of soybean gum in diets for broilers, with the the aim of evaluating its energy value and the best level of inclusion. Initially a metabolism trial were performed in stage 14 to 18 dayswere used 105 birds distributed in a completely randomized design with three treatments, one being the reference diet and two gum inclusion levels (10 and 15%) to determine the value of metabolizable energy and the coefficient of digestibility of diets. Based on the values of metabolizable energy experimental diets for Phase 1 to 42 days of age were formulated with increasing additions of soybean gum (0%, 2.5%, 5%, 7.5% and 10%); the birds were distributed in a completely randomized design with five treatments and four replicates of 20 birds each, mixed batch being half of each sex. We evaluated feed intake, weight gain, feed conversion, calorie intake, calorie conversion, carcass yield and higher socioeconomic diets. The variables were evaluated and in case of statistical significance, means were compared by the Student-Newman-Keuls test at 5% probability. The inclusion of soybean gum did not affect feed intake and calorie consumption (p> 0.05) in turn weight gain was altered (p <0.05) in the initial and growth phases and feed conversion suffered changes (p <0.05) at all stages except the final stage. The higher economic level for the inclusion of soybean gum was 1.75%